-27=x+9

Simple and best practice solution for -27=x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -27=x+9 equation:


Simplifying
-27 = x + 9

Reorder the terms:
-27 = 9 + x

Solving
-27 = 9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-27 + -1x = 9 + x + -1x

Combine like terms: x + -1x = 0
-27 + -1x = 9 + 0
-27 + -1x = 9

Add '27' to each side of the equation.
-27 + 27 + -1x = 9 + 27

Combine like terms: -27 + 27 = 0
0 + -1x = 9 + 27
-1x = 9 + 27

Combine like terms: 9 + 27 = 36
-1x = 36

Divide each side by '-1'.
x = -36

Simplifying
x = -36

See similar equations:

| txy=56 | | ln(x)+ln(x+29)=ln(62) | | X+6=-5x+30 | | -36t^2+18t=0 | | x^2y(xy-u)= | | -5(-3x-3x)=5x-15 | | 2154.28*.08= | | 2(n+8)=-18 | | x*0.07=150.80 | | X-(3-4)-1=5x-9-x | | 5x-5=6+6x | | 1/6m=20 | | (x+5)(-4x-2)(2x-1)=x | | 23n+10m+2n=180 | | 6m(m+4)=5m-15 | | 6m=20 | | 2x9/3 | | 2x^6+23x-25=0 | | y=-1+.5x | | 0.3x-8.1=-3 | | 0.9n+5.87=5.19-1.1n | | -49+6x=-3x+68 | | -11c-4=15 | | 3-4i=-2x+8yi | | 25=5(r-7)-7(6+8r) | | -27+5x=29-2x | | 0.25t+30=59.50 | | 61=2x | | 4s-15=19 | | -11-4=15 | | 29=-9(4d+7) | | 4x-5=-2x+7 |

Equations solver categories